Personal Factors, Social Support with Mental Health Literacy among Vocational Students - Tasod, Sukanya; Keawmungmueang, Pronpawee; Nuchsutham, Wilaiporn; Chaisin, Warunee (Journal of The Royal Thai Army Nurses, 2025)
The purpose of this research was to study personal factors, social support, mental health literacy and the relationship between social support and mental health literacy among vocational students. Participants included 127 vocational students who are between 16-20 years old. The data was collected between February to March 2024. The research tools were demographic questionnaire, Mental health literacy questionnaire and social support questionnaire. The data were analyzed using descriptive statistics, Spearman rank correlation coefficient and Chi-square test. The result showed that most of vocational students had moderate level of social support (70.08%) and almost half of vocational students had moderate level of mental health literacy (47.24%). There was a positive correlation of social support with mental health literacy (r=.19, p<.05). There was no statistically significant relationship between personal factor and mental health literacy. This finding can be used in planning care for mental health problems in vocational students.